The Role Of Teachers In Building Discipline And Responsibility Character In Students Through Islamic-Based Thematic Learning: The Role Of Teachers In Building Discipline And Responsibility Character In Students Through Islamic-Based Thematic Learning - Apriyadi, Ridho; Fisman Bedi (al-Iltizam: Jurnal Pendidikan Agama Islam, 2024)
The purpose of this research is to examine how teachers play a role in instilling values of discipline and responsibility in students during Islamic-based thematic learning. In an increasingly complex educational world, teachers must not only inform students but also teach them the positive traits that are essential for their personal and social development. This qualitative study uses interviews, classroom observations, and teaching material analysis for data collection. The research results show that Islamic-based thematic learning incorporates religious values into the learning process, thereby helping to build students' discipline and responsibility. By being a role model, implementing structured routines, and providing a supportive learning environment, teachers play a very important role. Moreover, when Islamic values are incorporated into thematic lessons, students show more responsibility and adherence to rules. This study emphasizes that character education requires a holistic approach. This approach combines daily lessons with religious principles to help students develop into disciplined and responsible individuals.